Circadian rhythms and the gut microbiota: from the metabolic syndrome to cancer - Bishehsari, Faraz (Nat Rev Endocrinol, 2020)
The metabolic syndrome is prevalent in developed nations and accounts for the largest burden of non-communicable diseases worldwide. The metabolic syndrome has direct effects on health and increases the risk of developing cancer. Lifestyle factors that are known to promote the metabolic syndrome generally cause pro-inflammatory alterations in microbiota communities in the intestine. Indeed, alterations to the structure and function of intestinal microbiota are sufficient to promote the metabolic syndrome, inflammation and cancer. Among the lifestyle factors that are associated with the metabolic syndrome, disruption of the circadian system, known as circadian dysrhythmia, is increasingly common. Disruption of the circadian system can alter microbiome communities and can perturb host metabolism, energy homeostasis and inflammatory pathways, which leads to the metabolic syndrome. This Perspective discusses the role of intestinal microbiota and microbial metabolites in mediating the effects of disruption of circadian rhythms on human health.